AAV-mediated chronic over-expression of SNAP-25 in adult rat dorsal hippocampus impairs memory-associated synaptic plasticity - McKee, Alex G.; Loscher, Jennifer S.; O'Sullivan, Niamh C.; Chadderton, Naomi; Palfi, Arpad; Batti, Laura; Sheridan, Graham K.; O'Shea, Sean; Moran, Mary; McCabe, Olive; Fernández, Alfonso Blanco; Pangalos, Menelas N.; et al. (Journal of Neurochemistry, 2010)
Long-term memory is formed by alterations in glutamate-dependent excitatory synaptic transmission, which is in turn regulated by synaptosomal protein of 25 kDa (SNAP-25), a key component of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor complex essential for exocytosis of neurotransmitter-filled synaptic vesicles. Both reduced and excessive SNAP-25 activity has been implicated in various disease states that involve cognitive dysfunctions such as attention deficit hyperactivity disorder, schizophrenia and Alzheimer's disease. Here, we over-express SNAP-25 in the adult rat dorsal hippocampus by infusion of a recombinant adenoassociated virus vector, to evaluate the consequence of late adolescent-adult dysfunction of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor protein in the absence of developmental disruption. We report a specific and significant increase in the levels of extracellular glutamate detectable by microdialysis and a reduction in paired-pulse facilitation in the hippocampus. In addition, SNAP-25 over-expression produced cognitive deficits, delaying acquisition of a spatial map in the water maze and impairing contextual fear conditioning, both tasks known to be dorsal hippocampal dependent. The high background transmission state and pre-synaptic dysfunction likely result in interference with requisite synapse selection during spatial and fear memory consolidation. Together these studies provide the first evidence that excess SNAP-25 activity, restricted to the adult period, is sufficient to mediate significant deficits in the memory formation process. Â© 2009 International Society for Neurochemistry.